Relative Performance and Karnal Bunt Infestation of Wheat (Triticum Aestivum L. Em. Thell.) Accessions in Eastern Uttar Pradesh. (Global Journal of Science Frontier Research, 2023)
Twenty wheat accessions were evaluated on 11 parameters in an experiment at Center for Research and Development CRD Gaunar Usaraha Gorakhpur U P in a randomized block design with three replications The objectives of the experiment were to assess the relative performance of the accessions on various parameters and extent of Karnal bunt KB infestation Normalized cumulative ranks were used to assess the relative performance of accessions KOH seed soaking technique was used to assess the extent of Karnal bunt infestation Based on normalized accumulating ranks the performance order of wheat accessions is BHU-25 HPST-16-17-16 HPAN-101 HPAN-57 PBW-677 CRD Gehu 1 BHU-31 ANKUR HPST-16-17-07 HPAN-111 HPAN-127 HPAN-65 HPST-16-17-15 PBW-Zn 1 HPAN-42 HPAN-164 HD-2967 WB-02 ZINCOL and HPAN-147 All the 20 accessions of wheat were susceptible to Karnal bunt and infestation ranged from 3 67 HPST-16-17-15 to 70 33 HPAN-147 High performers and least bunt infested accessions like BHU-25 HPST-16-17-16 HPAN-101 HPAN-57 and PBW-677 could be further investigated or directly recommended for cultivation in this area
Keywords: ideotype; karnal bunt; normalized cumulative ranks; selection